2021
DOI: 10.1093/mnras/stab2440
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter density profiles in dwarf galaxies: linking Jeans modelling systematics and observation

Abstract: The distribution of dark matter in dwarf galaxies can have important implications on our understanding of galaxy formation as well as the particle physics properties of dark matter. However, accurately characterizing the dark matter content of dwarf galaxies is challenging due to limited data and complex dynamics that are difficult to accurately model. In this paper, we apply spherical Jeans modeling to simulated stellar kinematic data of spherical, isotropic dwarf galaxies with the goal of identifying the fut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 144 publications
0
13
0
Order By: Relevance
“…For simplicity, throughout this work we set Gaussian priors of unit variance on every parameter, i.e., F prior is the identity matrix. While flat priors (e.g., Acquaviva et al 2012;Read & Steger 2017;Read et al 2018;Read et al 2021;Hayashi et al 2020;Chang & Necib 2021) are used in practice, Gaussian priors allow us to do this calculation analytically. Since priors can bias the results of an MCMC analysis we analyze choice of priors in Section 4.4 and show that our final results do not depend strongly on the choice of priors when the kinematic samples are larger than 100 stars.…”
Section: Priorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For simplicity, throughout this work we set Gaussian priors of unit variance on every parameter, i.e., F prior is the identity matrix. While flat priors (e.g., Acquaviva et al 2012;Read & Steger 2017;Read et al 2018;Read et al 2021;Hayashi et al 2020;Chang & Necib 2021) are used in practice, Gaussian priors allow us to do this calculation analytically. Since priors can bias the results of an MCMC analysis we analyze choice of priors in Section 4.4 and show that our final results do not depend strongly on the choice of priors when the kinematic samples are larger than 100 stars.…”
Section: Priorsmentioning
confidence: 99%
“…In this paper we study the prospects for precisely measuring the dark matter density profiles of dSphs, projecting what will be possible with current and future measurements of radial velocities and proper motions. While recent work has focused on using mock observations to explore similar questions (e.g., Chang & Necib 2021;Read et al 2021), this paper extends the work of Strigari et al (2007), using information theory, specifically the Fisher Information Matrix formalism, to predict uncertainties on important model parameters. Fisher formalism allows us to forecast parameter uncertainties without running a full computational-intensive likelihood analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Systematics in background estimation at the dwarf position are traditionally not taken into account, but worsen the limits by another factor 2-3 [74]. More recently, more substantial systematic issues have been pointed out which are important for understanding potential DM signals in dwarfs [75,76]. These are crucial to understand and accurately account for.…”
Section: Finding a Consistent Dm Signal Elsewherementioning
confidence: 99%
“…Moreover, a recent study highlights the need for a large number of kinematic member stars for dwarfs in order to accurately determine the DM inner profile [126]. By using mock observations, the authors showed that it is necessary to measure approximately 10,000 stars within a single dwarf galaxy to infer correctly the DM distribution at small scales.…”
Section: Dynamical Modelsmentioning
confidence: 99%